Liposome‐encapsulated superoxide dismutase mimetic: theranostic potential of an MR detectable and neuroprotective agent. (6th March 2014) - Shazeeb, Mohammed Salman; Feula, Giancarlo; Bogdanov, Alexei
<x xml:space="preserve">Abstract</x> Endogenous manganese based superoxide dismutase (Mn–SOD) provides the primary defense against excess production of potentially toxic superoxide anion (O2–). M40401 is a synthetic enzyme mimetic that has a catalytic activity rate exceeding that of the native SOD enzymes. The presence of a paramagnetic Mn(II) cation in M40401 suggests that the delivery and spatial distribution of this enzyme mimetic in vivo may be directly detectible using magnetic resonance imaging (MRI); however, the cardiotoxicity of Mn(II) severely limits the use of free M40401 in living systems. To deliver M40401 in vivo in amounts sufficient for MRI detection and to limit potential cardiotoxicity, we encapsulated M40401 into 170 nm liposomes composed of phosphatidylcholine and PEGylated phosphatidylethanolamine to achieve extended circulation in the bloodstream. The obtained liposomes efficiently catalyzed superoxide dismutation in vitro. Using 3 T MRI we investigated the biokinetics of liposome‐encapsulated M40401 in mice and found that, in addition to catalyzing superoxide dismutation in vitro, M40401 caused differential and region‐specific enhancement of mouse brain after systemic administration. Thus, liposome encapsulated M40401 is an ideal candidate for development as a theranostic compound useful for simultaneous MRI‐mediated tracking of delivery as well as for neuroprotective treatment of ischemic brain. Copyright © 2014 John Wiley & Sons, Ltd.